Social media reveal visitors' interest in flora and fauna species of a forest region. Issue 1 (31st December 2023) - Huertas Herrera, Alejandro; Toro-Manríquez, Mónica D.R.; Soler Esteban, Rosina; Lorenzo, Cristian; Lencinas, María Vanessa; Martínez Pastur, Guillermo
ABSTRACT: Visitor interests can be crucial to understanding humans' connectedness in nature. We analysed the relationship between people and flora and fauna species (native and exotic) through YouTube videos of a forest region (southern Patagonia) posted by visitors from different parts of the world. We characterised the species of flora and fauna observed by the visitors and calculated the time that appears in the videos as a proxy for their connectedness to biodiversity. The biodiversity observations were contrasted against visitors' sociodemographic characteristics (age and gender) by the Van der Waerden test and multivariate analyses. We created a sociogram that showed connections among species through visitor links to these data. Our results reveal different degrees of relationship between species, where some exotic ones were more preferred than natives (Van der Waerden test p = <0.100). Differences in the linkage to the flora and fauna species were related to the age and gender of the visitors. Visitor interests are modulated by access to ecosystem types (e.g. forests) and species' commonness/rarity and docility. Gender and age had less influence on the interests than expected, but it determined differential values on native and exotic diversity. Three groups of species emerged from the sociogram based on the visitor connectedness to flora and fauna species, evidencing high connections among native trees ( Nothofagus spp.), exotic beavers ( Castor canadensis ), and native geese and ducks (e.g. Chloephaga picta ). The novel approach utilised provides valuable data that can be used to test the influence of gender and age on the different biodiversity interests. This information has potential applications for nature conservation by detecting unsponsored biodiversity and ecosystem types that could be promoted, capturing the visitor interests, and improving the offer of visitor activities according to gender/age observations.